(untitled) (Journal of Namibian Studies : History Politics Culture, 2022)
Maternal and child health (MCH) stands as a pivotal concern in public health nursing, encompassing prenatal care, childbirth, postpartum support, and the overall well-being of infants, children, and adolescents. This paper delineates the significance of prioritizing MCH within public health nursing, emphasizing essential interventions, challenges, and the nurse’s role in enhancing outcomes for mothers and children.